2017
DOI: 10.1002/pat.4116
|View full text |Cite
|
Sign up to set email alerts
|

High‐strength electrically conductive fibers: Functionalization of polyamide, aramid, and polyester fibers with PEDOT polymer

Abstract: In this work, high-performance fibers such as aramid (Twaron), polyamide (PA6), polyester (PET), and hybrid Twaron/PA6 fibers were transformed into electroactive fibers by coating them with conjugated polymer, poly(3,4-ethylenedioxythiophene) (PEDOT) through vapor phase polymerization (VPP) method. The VPP is considered as an efficient technique for depositing CPs on different substrates regardless of their lower solubility in various solvents. In this paper, PEDOTcoated high-performance fibers were prepared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Hong et al carried out five cycles of in-situ polymerization of PEDOT on poly(trimethylene terephthalate) fabrics in the presence of ferric p-toluenesulfonic acid and ferric chloride as oxidants followed by butane treatment and obtained an electrical conductivity of 3.6 S/cm [79]. Bashir et al reported an electrically conductive polyester fabric with an electrical resistance of~2000 Ω, coated by PEDOT through oxidative vapor phase polymerization (VPP) in the presence of Fe (III) chloride hexahydrate oxidant [80]. They also obtained electro-conductive aramid, viscose and nylon fabrics by the same approach.…”
Section: Polymerization Of Pedot On the Textile Substratementioning
confidence: 99%
“…Hong et al carried out five cycles of in-situ polymerization of PEDOT on poly(trimethylene terephthalate) fabrics in the presence of ferric p-toluenesulfonic acid and ferric chloride as oxidants followed by butane treatment and obtained an electrical conductivity of 3.6 S/cm [79]. Bashir et al reported an electrically conductive polyester fabric with an electrical resistance of~2000 Ω, coated by PEDOT through oxidative vapor phase polymerization (VPP) in the presence of Fe (III) chloride hexahydrate oxidant [80]. They also obtained electro-conductive aramid, viscose and nylon fabrics by the same approach.…”
Section: Polymerization Of Pedot On the Textile Substratementioning
confidence: 99%
“…Therefore, many efforts have been made over the last decades to develop various textile electronics for wearable human−machine interfaces, biomedical applications, and smart sportswear . In this regard, stretchable and wearable electronic devices in the 1D form, which can be directly integrated into daily clothes without any inconsistency, are greatly promising for future wearable electronics . In addition, the hierarchical property of the fibrous structures (fiber: a small and short piece of a strand, filament: a long strand, yarn: an intertwined 1D structure of fibers or filaments, and fabric: a flexible substance consisting of a network of yarns) makes 1D electronic devices and systems remarkably suitable for advanced wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the continuous melt-spinning process was used to prepare the PTFE fiber, the fiber showed low mechanical strength compared to typical polymerbased fibers, such as polyethylene terephthalate (PET), polyamide (PA6), and polypropylene (PP). [29][30][31][32] We therefore tried the post-thermal drawing process to not only reduce density but also enhance orientation of the polymer chain, resulting in increased crystallinity and mechanical strength. The thermal drawing was conducted in the stretching zone (between rollers 3 and 4, see Figure 3(a)) at 155 C. We defined the thermal drawing ratio of the PTFE fibers from the speed of the fast (4)/slow (3) roller.…”
Section: Post-thermal Drawing Process Of Ptfe Fibermentioning
confidence: 99%